1992
DOI: 10.1113/jphysiol.1992.sp019285
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal changes in T‐type calcium current density in rat atrial myocytes.

Abstract: SUMMARY1. Postnatal changes in Ca2+ current were studied in voltage clamped atrial myocytes isolated from Sprague-Dawley rats. T-and L-type Ca2+ currents were identified using standard electrophysiological and pharmacological techniques. Cells were studied from seven groups of male and six groups of female rats ranging in age from 3 to 14 weeks.2. The density of atrial T-type Ca2+ current showed significant variation during postnatal development, with a maximum density reached at 4 5-5 weeks. At this age, T-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 29 publications
3
40
1
1
Order By: Relevance
“…frog, calf, cat, rabbit, ferret, mouse, rat, human (Argibay et al, 1988;Bean, 1989;Nuss and Houser, 1993;Yuan and Bers, 1994;Yuan et al, 1996;Nascimento, 1996;Li et al, 1999;Chen et al, 2002) but has been described in modest amounts in guineapig (Mitra and Morad, 1986;Sipido et al, 1998a). I CaT is present in atrial myocytes from frog, dog, cat, rat and guinea pig (Wu and Lipsius, 1990;Romanin et al, 1992;Xu and Best, 1992;Alvarez et al, 1996;Yue et al, 1999), but not human (Ouadid et al, 1991), heart.…”
Section: Working Cells (Ventricular Atrial)mentioning
confidence: 99%
“…frog, calf, cat, rabbit, ferret, mouse, rat, human (Argibay et al, 1988;Bean, 1989;Nuss and Houser, 1993;Yuan and Bers, 1994;Yuan et al, 1996;Nascimento, 1996;Li et al, 1999;Chen et al, 2002) but has been described in modest amounts in guineapig (Mitra and Morad, 1986;Sipido et al, 1998a). I CaT is present in atrial myocytes from frog, dog, cat, rat and guinea pig (Wu and Lipsius, 1990;Romanin et al, 1992;Xu and Best, 1992;Alvarez et al, 1996;Yue et al, 1999), but not human (Ouadid et al, 1991), heart.…”
Section: Working Cells (Ventricular Atrial)mentioning
confidence: 99%
“…In immature or developing cardiomyocytes, the appearance of T-type Ca 2ϩ current is relatively high. For example, during the postnatal development of rat atrial myocytes, the density of T-type Ca 2ϩ current is well correlated with growth rate [12]. It appears that an increased expression of Ttype current is closely related to cellular growth and/or hypertrophy.…”
Section: Development Of Excitation-contraction Coupling In Cardiomyocmentioning
confidence: 99%
“…Recent reports have shown that T-type Ca 2ϩ currents not only contribute to pacemaking (Irisawa et al 1993) but also might be able to more directly trigger Ca 2ϩ release from sarcoplasmic reticulum in guinea pig (Sipido et al 1998) and canine Purkinje myocytes (Zhou and January 1998). In this regard, it might be interesting to investigate the IGF-induced T-type currents (Piedras-Rentería et al 1997), which perhaps are involved in peptide hormone secretion during differentiation of the atrial myocytes in culture (Xu and Best 1992). Future experiments might elucidate such a function using ␣1E-specific peptide toxins (Newcomb et al 1998).…”
Section: Detection Of ␣1e By Immunoblottingmentioning
confidence: 99%
“…Originally, the IGF-induced T-type Ca 2 ϩ current in heart has been related to ␣ 1E-induced Ca 2 ϩ inward currents, because antisense oligonucleotides against ␣ 1E mRNA inhibited the IGF-induced T-type current (Piedras-Rentería et al 1997). This T-type current is believed to be important mainly during development (Kawano and DeHaan 1991;Xu and Best 1992). Because recombinant ␣ 1E is not considered a typical T-type current (Randall and Tsien 1997;Nakashima et al 1998), the immunodetection of ␣ 1E as a method independent of RT-PCR amplification (Piedras-Rentería et al 1997;Mitchell et al 1999) should give additional insight into a possible physiological role for ␣ 1E in heart.…”
mentioning
confidence: 99%